Nature. Survivors of the firestorm [videorecording (DVD)]. (PBS Home Video, 2011)
Australia's bushfires that tore through Victoria in 2009 incinerated over a million acres of land, including mountain ash forest ecosystems. The immediate aftermath of this firestorm was devastation, millions of animals died. But burned and traumatized survivors nursed back to health at wildlife hospitals showed an ability to bounce back, and the damaged environment demonstrated an extraordinary capacity for healing itself.